2003
DOI: 10.7124/bc.00065a
|View full text |Cite
|
Sign up to set email alerts
|

Usage of new bacterial adjuvants for vaccination by anti-influenza and anti-poliomyelitis vaccines

Abstract: Институт эпидемиологии и инфекционных болезней АМН Украины Спуск Протасов Яр, 4, Киев, 03038, Украина Институт микробиологии и вирусологии НАН Украины Ул. Академика Заболотного, 154, Киев, 03143, Украина 2 Институт молекулярной биологии и генетики НАН Украины Ул. Академика Заболотного, 150, Киев, 03143, Украина Проведено сравнение активности бактериальных адъювантов -нейрамининов Staphylococcus au reus, Streptococcus pneumoniae и Bacillus subtilis 105 no их способности влиять на иммунный ответ при вакцинации в… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Studies indicate Bacillus subtilis 3 is not only effective for the prevention and treatment of influenza but also helpful in the prevention and treatment of bacterial infections in both animal models [77,78] and humans [78,79]. The antibacterial property of this strain is due to its ability to produce an antibiotic named aminocoumarin which can suppress a wide range of pathogens and also strengthen host resistance [80]. Furthermore, a double-blinded, placebo-controlled trial of the combination of different probiotic strains containing Lacticaseibacillus paracasei subsp.…”
Section: Influenzamentioning
confidence: 99%
“…Studies indicate Bacillus subtilis 3 is not only effective for the prevention and treatment of influenza but also helpful in the prevention and treatment of bacterial infections in both animal models [77,78] and humans [78,79]. The antibacterial property of this strain is due to its ability to produce an antibiotic named aminocoumarin which can suppress a wide range of pathogens and also strengthen host resistance [80]. Furthermore, a double-blinded, placebo-controlled trial of the combination of different probiotic strains containing Lacticaseibacillus paracasei subsp.…”
Section: Influenzamentioning
confidence: 99%
“…the production of antibiotic aminocoumacin with a broad spectrum of pathogen suppression (18) and with the stimulation of immune resistance of the host (19). Previously, we found that some bacteria can produce peptides mimicking hemagglutinin of the influenza virus (20).…”
mentioning
confidence: 99%